SUHU TERBAIK UNTUK MENINGKATKAN PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH KEPITING BAKAU Scylla serrata DI SISTEM RESIRKULASI - Yuni Puji Hastuti; Ridwan Affandi; Radhita Millaty; Wildan Nurussalam; Siska Tridesianti (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2019)
One of the abiotic factors that affects the growth and the survival of mud crabs is temperature. The optimum temperature media will result in increasing of growth rate and survival rate on mud crabs Scylla serrata because it is related to the metabolism process. This study aimed to examine the effect of temperature on the survival rate (SR) and spesific growth rate (SGR) of mud crab through the reaction of physiological condition. This study consisted of the treatments with the temperature of 25 °C (A), the temperature of 27 °C (B), the temperature of 29 °C (C), dan the temperature of 31 °C (D). Based on the research result obtained 29 °C is the best temperature for the maintenance of mud crab with recirculation system, this can be seen from the result of feed conversion ratio, specific growth and survival of mud crab that have the best than other treatments.